Pengaruh Dosis Pupuk Fosfor dan Kalium Terhadap Pertumbuhan dan Hasil Tanaman Talas (Colocasia esculenta L. Schott var. Antiquorum) - Afifah Keumala; Nurhayati Nurhayati; Mardhiah Hayati (Fakultas Pertanian, Universitas Syiah Kuala, 2019)
Abstrak. Tujuan penelitian ini adalah untuk mengetahui pengaruh pemberian dosis pupuk fosfor dan kalium serta interaksi keduanya terhadap pertumbuhan dan hasil tanaman talas. Penelitian ini dilakukan di Kebun Percobaan 2 dan Laboratorium Fisiologi Tumbuhan Fakultas Pertanian Universitas Syiah Kuala Darussalam Banda Aceh dari bulan Februari sampai Agustus 2018. Unit-unit penelitian disusun berdasarkan Rancangan Acak Kelompok pola faktorial 3x3 dengan 3 ulangan dan dilanjutkan dengan uji Beda Nyata terkecil taraf 5% pada hasil uji F yang signifikan. Adapun faktor yang diteliti adalah dosis pupuk fosfor 3 taraf yaitu 100, 200 dan 300 kg SP36 ha-1 dan dosis kalium 3 taraf yaitu 200, 300, dan 400 kg KCl ha-1. Dosis fosfor berpengaruh sangat nyata terhadap jumlah daun tanaman talas umur 2 dan 10 MST serta bobot umbi basah dan berpengaruh nyata terhadap tinggi tanaman umur 2 MST, bobot berangkasan basah, dan jumlah umbi tanaman talas. Pertumbuhan dan hasil tanaman talas terbaik dijumpai pada dosis pupuk fosfor 200 kg ha-1. Dosis kalium berpengaruh sangat nyata terhadap jumlah daun tanaman umur 2 MST dan berpengaruh nyata terhadap bobot berangkasan basah tanaman talas. Pertumbuhan dan hasil tanaman talas terbaik dijumpai pada dosis kalium 300 kg ha-1. Terdapat interaksi yang tidak nyata antara perlakuan dosis fosfor dan dosis kalium terhadap pertumbuhan dan hasil tanaman talas.The Effect of Phosphorus and Potassium Fertilizer Doseson the Growth and Yield of Taro Plants (Colocasia esculenta L. Schott var. Antiquorum)Abstract. The purpose of this study was to determine the effect of dosing phosphorus and potassium fertilizers as well as their interactions with the growth and yield of taro plants. This research was carried out in Experimental Garden 2 and Laboratory of Plant Physiology, Faculty of Agriculture, Syiah Kuala Darussalam University, Banda Aceh from February to August 2018. The research units were compiled based on Randomized Block Design 3x3 factorial pattern with 3 replications and continued with Real Difference test Honest level of 5% on significant F test results. The factors studied were the dosage of phosphorus fertilizer with 3 levels, namely 100, 200 and 300 kg ha-1 and potassium doses with 3 levels namely 200, 300, and 400 kg ha-1. The dosage of phosphorus had a very significant effect on the number of leaves of taro plants aged 2 and 10 MST and the weight of wet tubers and significantly affected plant age 2 MST, wet weighted weight, and the number of taro tubers. The growth and yield of taro plants are best found at a dose of 200 kg ha-1 phosphorus fertilizer. The dosage of potassium fertilizer had a very significant effect on the number of plant leaves aged 2 MST and had a significant effect on the wet weight of taro plants. Growth and yield of taro plants are best found at potassium doses of 300 kg ha-1. There were no significant interactions between the treatment of phosphorus doses and potassium doses on the growth and yield of taro plants. Abstract. The purpose of this study was to determine the effect of dosing phosphorus and potassium fertilizers as well as their interactions with the growth and yield of taro plants. This research was carried out in Experimental Garden 2 and Laboratory of Plant Physiology, Faculty of Agriculture, Syiah Kuala Darussalam University, Banda Aceh from February to August 2018. The research units were compiled based on Randomized Block Design 3x3 factorial pattern with 3 replications and continued with Real Difference test Honest level of 5% on significant F test results. The factors studied were the dosage of phosphorus fertilizer with 3 levels, namely 100, 200 and 300 kg ha-1 and potassium doses with 3 levels namely 200, 300, and 400 kg ha-1. The dosage of phosphorus had a very significant effect on the number of leaves of taro plants aged 2 and 10 MST and the weight of wet tubers and significantly affected plant age 2 MST, wet weighted weight, and the number of taro tubers. The growth and yield of taro plants are best found at a dose of 200 kg ha-1 phosphorus fertilizer. The dosage of potassium fertilizer had a very significant effect on the number of plant leaves aged 2 MST and had a significant effect on the wet weight of taro plants. Growth and yield of taro plants are best found at potassium doses of 300 kg ha-1. There were no significant interactions between the treatment of phosphorus doses and potassium doses on the growth and yield of taro plants.